Low serum 25-hydroxyvitamin D level is associated with obesity and atherogenesis in adolescent boys - Junko Naganuma; Satomi Koyama; Osamu Arisaka; Shigemi Yoshihara (Korean Society of Pediatric Endocrinology, 2022)
Purpose We investigated the relationship of 25-hydroxyvitamin D (25[OH]D) level with obesity and atherosclerosis in Japanese adolescents. Methods We examined 492 children (247 boys and 245 girls) aged 12-13 years. The serum 25(OH)D level was compared among underweight, healthy weight, and overweight children. Spearman correlation coefficient analysis was performed to examine the relationships between the 25(OH)D level and body mass index (BMI), plasma lipids, and blood pressure and to compare the latter between the normal (≥20 ng/mL) and low (<20 ng/mL) 25(OH)D groups. Further, we performed a multiple regression analysis to assess the effect on the 25(OH)D level. Results The serum 25(OH)D level was significantly lower in overweight (20.5±2.7 ng/mL) than in healthy-weight boys (22.4±3.3 ng/mL) (P=0.004). Spearman correlation coefficients comparing the relationship of the 25(OH)D level with BMI, high-density lipoprotein cholesterol (HDL-C), and atherogenic index indicated significance in boys (ρ=-0.238 [P<0.0001], ρ=0.197 [P=0.002], and ρ=-0.146 [P=0.022], respectively). In boys, the multiple regression analysis results showed that BMI had negative and HDL-C had positive effects on the 25(OH)D level. The first was higher and the latter was lower in boys with low 25(OH)D level than in those with normal levels, respectively (P<0.05). No significant correlations were detected in girls. Conclusions Low serum 25(OH)D level was associated with obesity and increased atherogenic risk in adolescent boys only. This sex difference was probably mediated by body composition, sun exposure, estrogen, and adiponectin, which are characteristics of puberty.